Sociodemographic factors and lifestyle associated with abdominal obesity during middle adolescence in Mexico - Hernández-Mariano, José Ángel (2023)
Objective: To analyze the association between sociodemographic factors and lifestyle with the presence of abdominal obesity in middle adolescence in Hidalgo, Mexico. Method: Analytical cross-sectional study, carried out in a non-probabilistic sample of 172 adolescents between 15 and 18 years of age and of both sexes. Sociodemographic factors were identified through a general data questionnaire. Lifestyle information was obtained with the Lifestyle Profile questionnaire, made up of six dimensions: nutrition, exercise, health responsibility, stress management, interpersonal support, and self-actualization. Waist circumference was measured in centimeters and percentiles for each participant's age and sex were calculated; Those who presented a waist circumference ≥90th percentile were considered to have abdominal obesity. Associations were assessed using confounding-adjusted logistic regression models. Main results: 22.5% of the participants presented abdominal obesity. The odds of having this condition were higher in women (adjusted odds ratio [aOR] =2.46; p-value=0.02) and in those participants whose fathers (aOR=2.46; p-value=0.02) and mothers (aOR= 2.97; p-value=0.01) had a secondary school education or less. In addition, adolescents with a global overall lifestyle were more likely to present abdominal obesity (aOR= 5.69; p-value=0.01). Overall conclusion: Sex, parental education, and lifestyle were associated with higher odds of presenting abdominal obesity in the Mexican population during middle adolescence.